Proximity effect tunneling into high-TK Kondo alloys - I. M. Tang (2018)
The proximity effect tunneling into Kondo alloys is studied within the framework of the Matsuura, Ichinose, and Nagaoka (MIN) theory, which is valid for both low-TK Kondo alloys and high-TK Kondo alloys. By working with the two-particle propagators, the effects of both the repulsive interaction arising from the virtual polarization of the impurities in the ground state and the pair-breaking interactions on the decrease in the transition temperatures of the proximity effect sandwich can be clearly seen. It is found that the expression for the decrease for the sandwich containing low-TK Kondo impurities in the normal layer is similar to the expression obtained by Kaiser except for a redefinition of the pair-breaking parameter. For the high-TK Kondo impurities, the presence of the additional repulsive interaction in the MIN theory leads to an expression for the transition temperature decrease that is different from those previously obtained. The existence of a critical concentration of high-TK Kondo impurities in the normal layer at which the superconductivity of the sandwich is destroyed is seen to be directly connected to the presence of the contribution due to the repulsive interaction term in the expression for the decrease in the transition temperature. © 1984 Plenum Publishing Corporation.